The Beauty Terms Used in True Beauty Webtoon: The Word Formation Analysis - Sa'adah, Firda Rofiatus (English Literature Study Program, 2023)
The researcher conducted an analysis of the word-formation of beauty-related terms used in Yaongyi's Webtoon